HDAC4 in ischemic stroke: mechanisms and therapeutic potential - Kong, Qingsheng (Clin Epigenetics, 2018)
Stroke is one of the leading causes of death and disability worldwide, and the majority of the cases are ischemic stroke. However, it still lacks effective treatment except for thrombolytic therapy in an extremely narrow time window. Increased evidence suggests that histone deacetylase 4 (HDAC4) was dysregulated in ischemic stroke, which plays a key role in the pathogenesis of ischemic stroke and post-stroke recovery by affecting neuronal death, angiogenesis, and neurogenesis. Therefore, we aim to review the dysregulation of HDAC4 in ischemic stroke and the role of dysregulated HDAC4 in the pathogenesis of ischemic stroke. Furthermore, the therapeutic potential of modulating HDAC4 in ischemic stroke is discussed.